Pengaruh Penerapan E-Government Terhadap Kinerja Pegawai Sekretariat Dewan Perwakilan Rakyat Daerah Provinsi Sulawesi Utara - Christy Kurnia; JOHNNY POSUMAH; NOVVA PLANGITEN (Sam Ratulangi University, 2023)
This study aims to examine the effect of e-government implementation on employee performance at the Secretariat of the Regional People's Representative Council of North Sulawesi Province. The survey method is used to take samples from the population and collect data quantitatively. The data was processed by distributing questionnaires to employees of the Secretariat of the Regional People's Representative Council of North Sulawesi Province with a total population of 74 and a sample of 74 respondents. A basic linear regression analysis approach was applied in this investigation. The results of the study show that there is a positive influence between e-government and employee performance, so that the better the implementation of e-government, the better the employee performance. Keywords : e-Government, Employee, Performance